Evaluación de la fertilidad de un suelo mediante la producción de materia seca en ensayos de macetas. IV. Determinación de la fórmula de fertilización mediante Trifolium subterraneum y Lolium perenne x Lolium multiflorum - Schenkel S, G.; Floody A, T. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The nutritional deficiencies of a granitic soil, Santa Sofia, is determined by the use of Lolium perenne x Lolium multiflorum and Trifolium subterraneum in potted tests. Eight levels of lime and five fertilizer treatments were used. The choice of soil Santa Sofia was made because it belongs to one of the few Chilean soils which have responded to liming in field tests. The interpretation given to the chemical analysis of the soil and its fertility diagram, shows that the application of phosphorus, sulfur and potassium is required to obtain its potential fertility. Furthermore, it has been verified that calcium has a beneficial influence to improve the actual fertility of the soil. The effects produced by the addition of calcium and magnesium carbonate, was studied by means of fertilization treatments in two species. The influence of both factors over nutritional deficiency was almost null. The more outstanding deficiencies in the soil are phosphorus and sulfur. Potassium follows, independent the former and the latter of the species and lime levels considered. The absence of micronutrients will affect only the production of subterranean clover. Likewise, this species shows a high degree of sensitivity to the pH when the micronutrients are not added. This behavior of the subterranean clover is related to a shortage of boron and molybdenum. Its availability to plants is modified with the soil reaction obtained at different levels of lime incorporated to the soil.